Relationship of Hatching Egg Weights with Egg Weight Loss and DOC Weights of Chickens from Bangkok Male Crossbreeding with Pelung Chicken Broodstock - J. Junaedi; H. Husnaeni (Chalaza Journal of Animal Husbandry, 2020)
This study aims to determine the correlation between hatching egg weight with egg weight loss and DOC weight of Bangkok male crossbreed chickens with Pelung broodstock. This research uses a unit of automatic digital hatching machines (temperature regulation and automatic turning). The research material is Bangkok rooster chicken, amounting to two tails and four Pelung broilers. The chicken is crossed, and then the eggs are collected to be hatched eggs. This study uses digital camera tools, digital scales, and calculators. The coded eggs are hatched for 21 days. The parameters measured in this study were: Hatching egg weight (grams), egg weight of day 18th hatching, egg weight loss (%) / egg shrinkage, DOC weight, the correlation value between the weight of hatching eggs with egg weight loss, the correlation value between the weight of hatching eggs with the weight of DOC. Data analysis using correlation. The results obtained were the average hatching egg weight of 45.91 ± 3.75 grams, the average of hatching eggs on the 18th day 41.13 ± 3.43 grams, egg weight loss 10.40 ± 0.56%, weight DOC 35.36 ± 3.33 grams, correlation of hatching egg weight to DOC0.98 weight, hatching egg correlation with egg weight loss -0.25. Based on the results of the study,  it can be concluded that the characteristics of Bangkok crossbreed hatching eggs with Pelung brooders are in the normal range.  The correlation of hatching egg weight with very high DOC weight and positively correlated, correlation of hatching egg weight with low egg weight loss and negatively correlated.